Disrupting diagnostic hegemony: reimagining mental health language with British South Asian communities - Pranjol, Md. Zahidul I.; Amir, Alia (Frontiers in Education, 2025)
This perspective paper draws attention toward an urgent issue, that is, decolonizing mental health language for South Asian communities. A quarter of the world speaks at least one South Asian language including the global South Asian diaspora and the British South Asian communities in the UK. In the wake of the spread of the British Raj, English language and the Western medicine through it, a lingering gap persists between the language of western medicine and medical care for South Asian communities, especially the terminologies used for mental health language. In addressing the complexities of cross-cultural psychiatry and psychiatric anthropology, it has for nearly five decades engaged with the cultural relativity of psychopathology. This body of work provides valuable insights into the nuanced ways in which mental health is understood and experienced in diverse cultural contexts. In this perspective paper, we highlight the linguistic colonial injustices and suggest some approaches to developing culturally relevant mental health terminology. Moreover, we aim to contribute to this discourse by focusing on the specific linguistic challenges faced by South Asian communities.